Fabrication of Sophisticated Microstructures using Weak Support in 3D Printing. Issue 2 (8th December 2021) - Yu, Zhongwei; Deng, Xinghong; Shao, Guangbin; Li, Longqiu
Abstract: Projection‐based stereolithography (PSL) is one of the most competitive 3D printing technologies in fabricating complex microstructures because of its high accuracy and remarkable efficiency. Due to the layer‐by‐layer forming manner, some structures with cantilever features tend to collapse in the PSL process, for which support structures are required. However, the design, adding, and post‐treatment of traditional support structures can be extremely time‐consuming, and the manual removal step is always destructive and sometimes impossible, thus not suitable for sophisticated microstructures. Here a simple 3D printing method is proposed to fabricate sophisticated microstructures rapidly and precisely using weak support. Grayscale projection is used to produce partially cured photopolymer as weak support, which fills the lower space of overhanging structures and is constrained by a fully cured wall structure. The weak support is sufficient to support the printed parts while easy to remove because of incomplete photocured state. To determine the curing state of weak support, curing characteristics of the resin are measured and the relationship between curing energy and support effectiveness is investigated. Improvement in efficiency and applicability is observed in fabricating sophisticated microstructures using weak support method, which gives a promising solution to fabricate fragile microstructures with inaccessible overhang characteristics. Abstract : A weak support method is proposed in projection‐based stereolithography process to address the problem that traditional support methods are difficult or even impossible in fabricating complex microstructures with overhang features. The proposed method isexperimentally proved to be applicable in manufacturing microstructures with even suspended part, giving a promising solution to fabricate fragile microstructures and structures with inaccessible overhang characteristics.